The quality-weighted matching function - Gartner, Hermann,Rothe, Thomas,Weber, Enzo (Institute for Employment Research of the Federal Employment Agency, 2019)
We evaluate the quantity-quality trade-off on the labor market by estimating an augmented matching function weighting the matches by quality measures. We use the approach to evaluate the German labor market reforms conducted between 2003 and 2005. Indeed, we find a significant quantity-quality trade-off. However, even after controlling for job quality, a good half of the positive effect of reforms on the matching efficiency remains. Wir analysieren den Zielkonflikt zwischen Umfang und Qualität der Beschäftigung, indem wir eine erweiterte Matching-Funktion schätzen, worin die Zahl der neue Beschäftigungsverhältnisse (Matches) mit deren Qualität gewichtet wird. Diesen Ansatz verwenden wir, um die Auswirkungen der Hartz-Reformen der Jahre 2003 bis 2005 auf den Arbeitsmarkt zu bewerten. In der Tat bestätigt sich, dass ein Teil der zusätzlichen Beschäftigungsverhältnisse durch schlechtere Qualität erkauftfi war. Auch bei konstanter Qualität der neuen Matches wäre aber gut die Hälfte fides positiven Effektes auf die Matchingeffizienz infolge der Hartz-Reformen verblieben.
10419/222384
Keywords: Graue Literatur; matching approach; quantity-quality trade-off; labor market reforms; Germany